Hubungan Antara Komunikasi Antar Pribadi Guru dan Motivasi Kerja Guru Dengan Kinerja Guru di SD KARTIKA XIX-6 - Astia Aprina; Yiyin Bayinah; Johan Arifin; Efrita Norman (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the relationship between teachers' interpersonal communication, work motivation, and teacher performance at SD Kartika XIX-6, a private school that faces different challenges compared to state schools. Teacher performance is an important factor in determining the quality of education, which is influenced by communication effectiveness and work motivation. Good communication between teachers plays an important role in building collaboration, supporting the exchange of ideas, and providing emotional support. This can increase teacher morale and motivation in facing teaching challenges. In addition, high work motivation, which is influenced by the support of colleagues and leaders, as well as the existence of both financial and non-financial incentives, directly contributes to increasing teaching effectiveness and student learning outcomes. This research uses a case study approach with descriptive quantitative methods, collecting data through direct interviews with teachers at SD Kartika XIX-6. The research results show that there is a significant positive relationship between effective communication, work motivation, and increased teacher performance. It is hoped that this study can contribute to the development of effective strategies to improve teacher performance, especially in private schools.